Optimalisasi Server Proxmox Pada Nict Uin Syarif Hidayatullah Jakarta - Achmad Fachri; Neforawati, Indri; Kurniawan, Asep (POLITEKNIK NEGERI JAKARTA, 2021)
Servers are needed as a network infrastructure that supports services at various companies, the more services needed, the more servers are needed. The number of servers needed also requires a large fee. It takes a Cluster system on the Proxmox server so that the required services are run on a virtual machine so that each server can run various services and reduce the need for physical servers. The Proxmox server cluster system is implemented to be able to use a migration system that aims to move virtual machines from one node to another without stopping the services provided. The goal of moving virtual machines is to move virtual machines from nodes with small specifications to nodes with large specifications so that virtual machines can make better use of resources and the supported services continue to run.